Religionshistoriske og typologiske overvejelser over fænomenet askese - Klostergaard Petersen, Anders (Religionsvidenskabeligt Tidsskrift, 2016)
In the current article I raise the question of asceticism as a ubiquitous and multifarious phenomenon in human culture. Contrary to much traditional scholarship on asceticism within the history of religion that has focused almost exclusively on the phenomenon as confined to a Judaeo-Christian and Indian context, I point to the importance of bringing the later phenomena into dialogue with previous examples in tribal and archaic types of religion. In anthropology there has from an early period been a strong acknowledgement of the pervasiveness of ascetic practices not least in conjunction with ritual. Yet, this appreciation has never really been taken into consideration by scholars working on subsequent forms of asceticism. By means of genealogically typological reflections, I aim to develop a full scale understanding that will enable us to take the entire gamut of ascetic practices and phenomena into consideration. My ruminations rest on a biocultural evolutionary approach that allows me, on the one hand, to account for the pluriform nature of the phenomenon under scrutiny and, on the other hand, to place emphasis on the uniting features. From this perspective, two points of transition come to the fore of discussion. The first crucial transformation pertaining to asceticism took place at the time of the emergence of axial age thinking and practice at which period asceticism changed from being ritually to be ideologically determined. The second decisive change occurred at the transition from post-axial age types of religion to modernity when the element of privation disappeared. I develop my understanding of the specific nature of asceticism pertinent to the singular stages in the history of asceticism in the wake of thinkers such as Robert Bellah, Peter Sloterdijk and Pierre Hadot.